Knowledge, Behavior, Attitude and Practice of Hospital Pharmacists to Adverse Drug Reactions in the Elderly in a Tertiary Hospital in Nigeria - Usifoh, Stella Folajole; Olutayo, Oluwakemi Abiodun (Indian Journal of Pharmacy Practice)
Introduction: Adverse drug reactions (ADRs) including interactions is a drug therapy problem worldwide in the elderly and are a common cause of hospitalization. Objectives: To assess the knowledge, behavior and attitude of hospital pharmacists to adverse drug reactions in elderly patients in University College Hospital (UCH), Ibadan. Methods: A descriptive cross-sectional random sampling of 100 pharmacists in UCH, Ibadan with a selfadministered structured questionnaire that assessed the knowledge on the safety of specific drugs, adverse drug reactions, behavior and attitude of pharmacists to ADRs reporting in the elderly. Results: The response rate was 95%, mean age was 37.55 ± 5.62; females were 53.7% and males 46.3%. The majority, 90.5% were married and 45.3% had a B.Pharm degree. Many 67.4% had poor knowledge of ADR; however, 63.2% within the age range of 31-40 years had good knowledge. Those trained in pharmacovigilance had a moderate knowledge of 22.2% while those without training had 50% of them with poor knowledge. Majority 86.3% did not have knowledge of STOPP/START as well as Beer’s criteria as a screening tool in the elder. However, the majority had good behavior and attitude on ADR reporting. There was statistical significance between knowledge score and age, cadre and training in pharmacovigilance with P-values of 0.012, 0.015 and 0.021 respectively. Conclusion: Many of the respondents had poor knowledge of ADR in the elderly but they have good behavior and attitude towards ADR reporting. Therefore, educational intervention for hospital Pharmacists on ADR in the elderly is needed.
Keywords: Adverse drug reaction; Elderly; Knowledge; Attitude; Behavior.